DENSITY AND DISTRIBUTION PATTERN OF SNAILS (Cerithidea quadrata) IN MANGROVE FOREST ANAK SETATAH VILLAGE KEPULAUAN MERANTI REGENCY OF RIAU PROVINCE by - Fainal Asandi; Sofyan Husein Siregar; Syafruddin Nasution (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research was conducted in July 2018 at Anak Setatah Village, West Rangsang Sub-District, Kepulauan Meranti Regency of Riau Province.This study aims determine the density and the distribution patte of C. quadrata.The research used survey method. There were 3 stations chosen by purposive samplingmethod. Each station was made 100m line transect. Each transect consist of 4 plots measuring 3m x 3m with the distance was 25m between low and hing waters. Samples were analyzed in the biology laboratory of Marine Science Departemen Riau University. Result show that the highest density of the snailswas at station II (4.92 ind/m²) fallowed by stations III (2.25 ind/m²) while the lowest density was at Stations I (1.3 ind/m²). There is a very strong relationship between organic sedimen content and density of C. quadrata( ). Keywords: Cerithidea quadrata, Distribution, Density, Mangrove, Anak Setatah